Plan de aseguramiento metrológico en los servicios de UCI y salas de cirugía para la clínica universidad de la sabana - León Rojas, Paula Camila. (Ingeniería Biomédica, 2021)
Introduction: At the Universidad de la Sabana Clinic, the need to evaluate the tools used in the maintenance and verification processes of biomedical equipment was identified. This in order to identify within the current regulations in Colombia that biomedical equipment requires calibration processes or performance evaluation. Therefore, it is proposed to carry out a metrological assurance plan, where all the information on the technical specifications of the equipment present in the service is collected. Objective: Generate the metrological assurance plan in the intensive care unit (ICU) service and the surgery room service of the Universidad de la Sabana Clinic. Methodology: In order to generate a support tool for the Biomedical Engineering department in the process of the maintenance schedule for the year 2022. The creation of the metrological assurance plan is developed in 3 phases which allow the verification of the inventory in both services, compilation of technical specifications of the equipment to be evaluated, selection of equipment for calibration processes and those that will be handled through performance evaluation. Finally, an adaptation of existing formats to specific technologies is generated. Results: Inventory of ICU services and surgery rooms is validated, in order to identify the biomedical equipment of the services. From these, it was possible to recognize the equipment that requires calibration processes by a certified laboratory and the equipment submitted to performance evaluation. For all the biomedical equipment present in both services, the database is complemented where the technical specifications of each equipment are shown. And for the teams selected for the performance evaluation process, the corresponding formats were adapted. Conclusions: The database was adapted as part of the solution that allows identifying the biomedical equipment of the ICU services and surgery rooms. This format will allow the institution to organize the technology according to its technical file, as well as to identify if the biomedical equipment requires metrology processes or evaluation performance according to the regulations. When reviewing the documentation of the current metrology regulations in Colombia, it is found that there is no clarity of the processes that are carried out with each biomedical equipment according to its risk classification. This is why the equipment is chosen according to its operating principle to be subjected to a performance evaluation process. It is identified that the application process of the metrological assurance plan will allow the institution to start with a cost optimization process. It will guarantee compliance with current regulations, the reduction of adverse events due to biomedical equipment and the extension of years of useful life of the technology.

Introducción: En la Clínica Universidad de la Sabana se identificó la necesidad de evaluar las herramientas utilizadas en los procesos de mantenimientos y verificaciones de los equipos biomédicos. Esto con el fin de identificar dentro la normatividad vigente en Colombia que equipos biomédicos requieren procesos de calibración o evaluación de desempeño. Por lo que se propone realizar un plan de aseguramiento metrológico, donde se recopilara toda la información de especificaciones técnicas de los equipos presentes en el servicio. Objetivo: Generar el plan de aseguramiento metrológico en el servicio de unidad de cuidados intensivos (UCI) y el servicio de salas de cirugía de la Clínica Universidad de la Sabana. Metodología: Con el fin de generar una herramienta de apoyo para el departamento de Ingeniería Biomédica en el proceso del cronograma de mantenimiento del año 2022. Se da desarrollo a la creación del plan de aseguramiento metrológico en 3 fases las cuales permiten la verificación del inventario presente en ambos servicios, recopilación de especificaciones técnicas de los equipos a evaluar, selección de equipos para procesos de calibración y los que se manejarán mediante evaluación de desempeño. Por último, se genera una adaptación de los formatos existentes a tecnologías específicas. Resultados: Se valida inventario de los servicios UCI y de salas de cirugía, con el fin de identificar los equipos biomédicos de los servicios. A partir de estos, fue posible hacer el reconocimiento de los equipos que requieren procesos de calibración por laboratorio certificado y los equipos sometidos a evaluación de desempeño. Para todos los equipos biomédicos presentes en ambos servicios se complementa la base de datos donde se muestran las especificaciones técnicas de cada equipo. Y para los equipos seleccionados para proceso de evaluación de desempeño se adaptaron los formatos correspondientes. Conclusiones: Se adaptó base de datos como parte de la solución que permite identificar los equipos biomédicos de los servicios de UCI y salas de cirugía. Este formato permitirá a la institución organizar la tecnología de acuerdo a su ficha técnica, así como identificar si los equipos biomédicos requieren procesos de metrología o evaluación desempeño según la normativa. Al revisar la documentación de la normativa actual de metrología en Colombia, se encuentra que no se presenta claridad de los procesos que se llevan a cabo con cada equipo biomédico de acuerdo a su clasificación de riesgo. Es por esto que se eligen los equipos de acuerdo a su principio de funcionamiento para ser sometidos a un proceso de evaluación de desempeño. Se identifica que el proceso de aplicación del plan de aseguramiento metrológico permitirá a la institución iniciar con un proceso de optimización de costos. Garantizará el cumplimiento de la normativa vigente, la reducción de eventos adversos por equipos biomédicos y la prolongación de años de vida útil de la tecnología.
Keywords: Ingeniería Biomédica - Universidad de la sabana; Equipos médicos - Universidad de la sabana; Tecnología médica - Universidad de la sabana; Ingeniería Biomédica - Universidad de la sabana; Equipos médicos - Universidad de la sabana; Tecnología médica - Universidad de la sabana; Biomedical Engineering - Savannah University; Medical equipment - Savannah University; Medical Technology - Savannah University